Upaya pengembangan kuliner tradisional puluik pucung di Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi - Basri Basri; Yoserizal Yoserizal; Yesi Yesi (Unri Conference Series: Community Engagement, 2019)
The traditional cuisine is usually full of flavors and is typical of certain regions. An example is a Puluik pucung in Kuantan Mudik. Puluik Pucung has only been made to fill the event, even though the potential to be marketed commercially is quite high. This empowerment activity is carried out in Kuantan Mudik Subdistrict, Kuantan Singingi Regency. The target of this activity is the village apparatus, the people of Kuantan Mudik Village who have the ability to make the Puluik Pucung. The purpose of the community empowerment activities are to form the variety of flavors and ways of developing and marketing the puluik pucung, and finding suitable media as a means of developing and marketing. The results of community service can be seen from the ability of the participants' understanding of the material presented was very good as seen from the questions presented at the discussion session. Participants are able to absorb and respond to the material presented by the extension team related to the potential for development and marketing of puluik pucung. This activity also provides knowledge to participants about the right and correct ways to develop the potential of other traditional cuisines to be known and likely by outside communities.